2022
DOI: 10.1038/s41598-022-16939-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and complete genome analysis of a novel bacteriophage vB_EfaS-SRH2 against Enterococcus faecalis isolated from periodontitis patients

Abstract: Periodontitis is a chronic inflammatory condition that can damage soft tissues and supporting teeth. Enterococcus faecalis is an opportunistic pathogen usually living in the oral cavity and plays a critical role in apical periodontitis that significantly threatens human health. The use of bacteriophages as an alternative way to eliminate bacterial infections is a promising approach. E. faecalis was isolated from the depth of dental packets of patients with periodontitis. Antimicrobial susceptibility was tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
2
1
Order By: Relevance
“…To analyze the antimicrobial susceptibility, we employed a wide range of antibiotics, showing that our clinical isolate E. faecalis exhibited resistance to a large number of them, such as Erythromycin, Streptomycin, and Tetracycline; however, some antibiotics tested showed effectiveness against E. faecalis , such as Ampicillin, Ciprofloxacin, Daptomycin, Gentamicin, Penicillin, and Rifampicin. The aforementioned result differs from Pazhouhnia et al [ 60 ] since they reported a different pattern of antibiotic resistance in several E. faecalis -isolated strains from the root canal of individuals with periodontitis, demonstrating that both isolated strains, theirs and our clinical isolate of E. faecalis , are resistant to Tetracycline, one of the main components of CTZ paste. This highlights the variability in pathogenicity that can be found in different clinical isolates.…”
Section: Discussioncontrasting
confidence: 97%
“…To analyze the antimicrobial susceptibility, we employed a wide range of antibiotics, showing that our clinical isolate E. faecalis exhibited resistance to a large number of them, such as Erythromycin, Streptomycin, and Tetracycline; however, some antibiotics tested showed effectiveness against E. faecalis , such as Ampicillin, Ciprofloxacin, Daptomycin, Gentamicin, Penicillin, and Rifampicin. The aforementioned result differs from Pazhouhnia et al [ 60 ] since they reported a different pattern of antibiotic resistance in several E. faecalis -isolated strains from the root canal of individuals with periodontitis, demonstrating that both isolated strains, theirs and our clinical isolate of E. faecalis , are resistant to Tetracycline, one of the main components of CTZ paste. This highlights the variability in pathogenicity that can be found in different clinical isolates.…”
Section: Discussioncontrasting
confidence: 97%
“…Encouragingly, new bacteriophages against E. faecalis are still being isolated and characterized. For instance, vB_EfaS_LM99 [ 102 ] and vB_EfaS-SRH2 [ 103 ] have relatively narrow host ranges, while vB_EfaH_163 [ 104 ], vB_EfaS-Zip (Zip), and vB_EfaP-Max (Max) [ 105 ] exhibit a wide host lytic range, including both E. faecalis and E. faecium . In addition, vB_EfaS-271 [ 106 , 107 ] and vB_ZEFP [ 108 ] have been demonstrated to lyse E. faecalis in biofilms.…”
Section: Phage Therapy For Endodontic Infections Encounters Both Hurd...mentioning
confidence: 99%
“…Phage vB_EfaS‐SRH2 with an irregular pentagonal morphology of the head and a non‐contractile tail belonging to the Siphoviridae can lyse E. faecalis that is related to periodontitis and reduce biofilm mass. It has a DNA genome of 38,746 bp that encodes 62 putative open reading frames (ORFs) (Pazhouhnia et al., 2022). Phage ΦSG005 is a virulent phage against Streptococcus gordonii that resides in oral cavity and causes dental plaque formation (Loo et al., 2000).…”
Section: Predatory Bacteria and Phagesmentioning
confidence: 99%